Comparative Assessment of Well and Borehole Water Quality Index in Sokoto Metropolis (CaJoST, 2024)
The study focuses on the comparative assessment on the levels of somephysiochemical parameters of well and borehole water collected from fivelocations in Sokoto metropolis to ascertain their quality index. Samples werecollected randomly and analyzed using standard method of analysis. Thephysiochemical parameters analyzed include; pH, Turbidity, Total DissolvedSolids (TDS), Calcium (Ca2+), Magnesium (Mg2+), Chlorides (Cl-), Fluorides(F-) Sulphates (SO42+) and Nitrate (NO3-). The result of the study wassubjected to Descriptive statistics and water quality index. The descriptivestatistics results revealed that physicochemical parameters like pH, TDS,SO42-, and turbidity are within the WHO limit of drinking water whileparameters like Ca2+, Mg2+ and Cl- were within and not within the WHO limitin some sampling locations whereas parameters like F- and NO3- were foundnot within the WHO limit in all the sampling locations. The result shows thatboth water sources were found within excellent and very good water qualityindex respectively which indicates that both water sources (well andborehole water) consumed within Sokoto metropolis are safe and suitablefor drinking as it meets the minimum requirements of WHO standard ofdrinking water quality.